Grammar Skills in Learning a Foreign Language - Kambarova Dilnoza Musakulovna (Research Parks Publishing LLC, 2021)
Before learning any language, it is necessary to have a deep understanding of the grammatical concepts in it, because without grammatical skills it is difficult to speak, read and write. Grammar is the backbone of every language. Grammar, as a science, is also deeply ingrained and is part of linguistics. In particular, grammar plays an important role in learning foreign languages.